Disrupting neural activity related to awake-state sharp wave-ripple complexes prevents hippocampal learning - Nokia, Miriam S.; Mikkonen, Jarno E.; Penttonen, Markku; Wikgren, Jan (Frontiers in Behavioral Neuroscience, 2012)
Oscillations in hippocampal local-field potentials reflect the crucial involvement of the hippocampus in memory trace formation: theta (4-8 Hz) oscillations and ripples ( 200 Hz) occurring during sharp waves are thought to mediate encoding and consolidation, respectively. During sharp wave-ripple complexes (SPW-Rs), hippocampal cell firing closely follows the pattern that took place during the initial experience, most likely reflecting replay of that event. Disrupting hippocampal ripples using electrical stimulation either during training in awake animals or during sleep after training retards spatial learning. Here, adult rabbits were trained in trace eyeblink conditioning, a hippocampus-dependent associative learning task. A bright light was presented to the animals during the inter-trial interval, when awake, either during SPW-Rs or irrespective of their neural state. Learning was particularly poor when the light was presented following SPW-Rs. While the light did not disrupt the ripple itself, it elicited a theta-band oscillation, a state that does not usually coincide with SPW-Rs. Thus, it seems that consolidation depends on neuronal activity within and beyond the hippocampus taking place immediately after, but by no means limited to, hippocampal SPW-Rs.